Report on workshop on food and nutrition security in Jamaica in the 1980's and beyond (CFNI KingstonJA, 1986)
Summarizes the discussion of papers presented focussing on economic, sociological, and nutritional aspects of food and nutrition security. Some of the issues arising out of the discussion include the problem of food demand and supply. Emphasizes the need for the development and strengthening of coordinated planning among appropriate public and private sector bodies. Calls for the expansion of agricultural production by small, medium, and large scale farmers so as to earn additional foreign exchange & ensure food & nutrition security. Suggests that postharvest activities must be fully integrated with production activities. Recommends policies and programs designed to foster food & nutrition security at the national and household levels.
DC